Copolymer, and electroluminescent device material and electroluminescent device using said copolymer
Patent Information
- Application Number
- JP2020212454
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-12-22
- Publication Date
- 2025-03-26
- Estimated Expiration
- 2040-12-22
Smart Images

Figure 0007651296000047 
Figure 0007651296000001 
Figure 0007651296000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a copolymer, and an electroluminescence device material and an electroluminescence device using the copolymer. [Background technology]
[0002] Research and development of electroluminescence elements (EL elements) is being actively carried out. In particular, EL elements are considered to be promising for use as inexpensive solid-state light-emitting large-area full-color display elements and writing light source arrays. EL elements are light-emitting elements having a thin film of several nanometers to several hundred nanometers between an anode and a cathode. EL elements usually further have a hole transport layer, a light-emitting layer, an electron transport layer, and the like.
[0003] Among these, materials for the light-emitting layer include fluorescent materials and phosphorescent materials. Phosphorescent materials are expected to have higher luminous efficiency than fluorescent materials. In addition, to cover a wide color gamut, RGB light sources are required to have a narrow emission spectrum with a half-width. In particular, deep blue is required for blue, but currently no element has been found that satisfies the requirements for long life and color purity.
[0004] As a method for solving these problems, there is a light-emitting device that uses "quantum dots," an inorganic light-emitting material, as a light-emitting material (Patent Document 1). Quantum dots (QDs) are semiconductor materials with a crystal structure of several nanometers in size, and are composed of hundreds to thousands of atoms. Quantum dots have a large surface area per unit volume because they are very small in size. Therefore, most of the atoms are present on the surface of the nanocrystals, and they exhibit quantum confinement effects. Due to this quantum confinement effect, quantum dots can adjust the emission wavelength simply by adjusting their size, and have characteristics such as excellent color purity and high PL (photoluminescence) emission efficiency, so they have attracted much attention. A quantum dot light-emitting diode (QD LED) is known to have a three-layer structure including a quantum dot emission layer in between, a hole transport layer (HTL) and an electron transport layer (ETL) on both sides. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2010-199067 A Summary of the Invention [Problem to be solved by the invention]
[0006] However, an electroluminescence device (particularly a quantum dot electroluminescence device) using the hole transport material described in Patent Document 1 has not been able to achieve sufficient performance (particularly luminous efficiency and durability).
[0007] Therefore, the present invention has been made in consideration of the above circumstances, and has an object to provide a technique capable of improving the luminous efficiency and durability (luminous life) of an electroluminescence element (particularly a quantum dot electroluminescence element). [Means for solving the problem]
[0008] The present inventors have conducted extensive research to solve the above problems, and as a result have found that the above problems can be solved by using a polymer having a specific structure, thereby completing the present invention.
[0009] That is, the above object can be achieved by a copolymer having a constitutional unit represented by the following formula (1) or (2).
[0010] [ka]
[0011] In the above formula (1) or (2), R 1 represents a substituted or unsubstituted alkyl group having from 1 to 20 carbon atoms, a substituted or unsubstituted monovalent aromatic hydrocarbon group having from 6 to 30 ring carbon atoms, a substituted or unsubstituted monovalent aromatic heterocyclic group having from 5 to 30 ring atoms, or -YN(Ar 2 )(Ar 3 ), in which Y represents a substituted or unsubstituted divalent aromatic hydrocarbon group having 6 to 30 ring carbon atoms, Ar 2 and Ar 3 each independently represents a substituted or unsubstituted monovalent aromatic hydrocarbon group having 6 to 30 ring carbon atoms, or a substituted or unsubstituted monovalent aromatic heterocyclic group having 5 to 30 ring atoms; R 2 and R 3each independently represents a substituted or unsubstituted alkyl group having from 1 to 20 carbon atoms, a substituted or unsubstituted alkoxy group having from 1 to 20 carbon atoms, a substituted or unsubstituted monovalent aromatic hydrocarbon group having from 6 to 30 ring carbon atoms, or a substituted or unsubstituted monovalent aromatic heterocyclic group having from 5 to 30 ring atoms, 2 and two R 3 may be the same or different from each other, and two R 2 and two R 3 may each be bonded to each other to form a ring; X 1 and X 2 each independently represents a carbon atom (C) or a silicon atom (Si); Ar 1 represents a substituted or unsubstituted divalent aromatic hydrocarbon group having 6 to 30 ring carbon atoms, or a substituted or unsubstituted divalent aromatic heterocyclic group having 5 to 30 ring atoms. Effect of the Invention
[0012] According to the present invention, it is possible to provide an electroluminescence element (particularly a quantum dot electroluminescence element) that is excellent in luminous efficiency and durability (luminescence life span). [Brief description of the drawings]
[0013] [Figure 1] FIG. 1 is a schematic diagram showing an electroluminescence element according to an embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] In a first aspect, the present invention provides a copolymer having a constitutional unit represented by the following formula (1) or (2):
[0015] [ka]
[0016] In the above formula (1) or (2), R 1 represents a substituted or unsubstituted alkyl group having from 1 to 20 carbon atoms, a substituted or unsubstituted monovalent aromatic hydrocarbon group having from 6 to 30 ring carbon atoms, a substituted or unsubstituted monovalent aromatic heterocyclic group having from 5 to 30 ring atoms, or -YN(Ar 2 )(Ar 3 ), in which Y represents a substituted or unsubstituted divalent aromatic hydrocarbon group having 6 to 30 ring carbon atoms, Ar 2 and Ar 3 each independently represents a substituted or unsubstituted monovalent aromatic hydrocarbon group having 6 to 30 ring carbon atoms, or a substituted or unsubstituted monovalent aromatic heterocyclic group having 5 to 30 ring atoms; R 2 and R 3 each independently represents a substituted or unsubstituted alkyl group having from 1 to 20 carbon atoms, a substituted or unsubstituted alkoxy group having from 1 to 20 carbon atoms, a substituted or unsubstituted monovalent aromatic hydrocarbon group having from 6 to 30 ring carbon atoms, or a substituted or unsubstituted monovalent aromatic heterocyclic group having from 5 to 30 ring atoms, 2 and two R 3 may be the same or different from each other, and two R 2 and two R 3 may each be bonded to each other to form a ring; X 1 and X 2 each independently represents a carbon atom (C) or a silicon atom (Si); Ar 1 represents a substituted or unsubstituted divalent aromatic hydrocarbon group having 6 to 30 ring carbon atoms, or a substituted or unsubstituted divalent aromatic heterocyclic group having 5 to 30 ring atoms.
[0017] In this specification, the "structural unit represented by the following formula (1)" is also referred to as the "structural unit (1)" or the "structural unit (1) according to the present invention." Similarly, in this specification, the "structural unit represented by the following formula (2)" is also referred to as the "structural unit (2)" or the "structural unit (2) according to the present invention."
[0018] In a second aspect, there is provided an electroluminescent device material comprising the copolymer according to the present invention.
[0019] In a third aspect, the present invention provides an electroluminescent element comprising a first electrode, a second electrode, and one or more organic films disposed between the first electrode and the second electrode, wherein at least one layer of the organic films comprises a copolymer according to the present invention.
[0020] In this specification, an electroluminescent element is also simply referred to as an "LED." A quantum dot electroluminescent element is also simply referred to as a "QLED." An organic electroluminescent element is also simply referred to as an "OLED."
[0021] The present inventors have conducted extensive research into electroluminescence devices (particularly quantum dot electroluminescence devices) that are excellent in luminous efficiency and durability (luminous lifetime). As a result, they have discovered that by having the structural unit of the above formula, a substance can be obtained that can achieve a good balance between luminous efficiency and durability (luminous lifetime). In particular, in the structural unit of formula (1) or (2), the carbazole ring in the main chain and the benzene ring in the side chain are connected to each other by X 1 (Formula (1)) or X 1 and X 2(Formula (2)). Such a crosslinked structure increases the bond dissociation energy of the C-N bond between the nitrogen atom of the carbazole ring in the main chain and the carbon atom of the benzene ring in the side chain to which the nitrogen atom is bonded in the excited state and anion state, making the substance less likely to decompose or not decompose even in the presence of holes and electrons. High hole resistance is maintained, and exciton resistance and electron resistance, which affect the device life, are strengthened. Therefore, by using the copolymer of the present invention in an electroluminescence device, durability (light-emitting life) can be improved.
[0022] In addition, by adopting the above-mentioned crosslinked structure, the dihedral angle of the C-N bond axis between the nitrogen atom of the carbazole ring of the main chain and the carbon atom of the benzene ring of the side chain to which the nitrogen atom is bonded becomes narrow. Therefore, the copolymer is easily stacked (packed) and can exist densely, so that the mobility of holes (positive holes) increases. Therefore, by using the copolymer according to the present invention in an electroluminescence element, the mobility of holes (positive holes) from the hole transport layer to the light emitting layer can be improved, and the light emitting efficiency can be improved.
[0023] Therefore, the copolymer according to the present invention exhibits excellent exciton resistance and electron resistance, as well as high hole mobility. Therefore, the electroluminescent device produced using the copolymer according to the present invention can exhibit a good balance between luminous efficiency and durability (long luminous life). In addition, the copolymer according to the present invention can suppress an increase in driving voltage. Therefore, the electroluminescent device produced using the copolymer according to the present invention can exhibit high luminous efficiency at a low driving voltage. In addition, since the copolymer according to the present invention has excellent film-forming properties and solvent solubility, it is possible to form a film by a wet (coating) method. Therefore, by using the copolymer according to the present invention, it is possible to increase the area of the electroluminescent device and increase the productivity. The above effect can be effectively exhibited when the copolymer according to the present invention is applied to an EL device, particularly a hole transport layer or hole injection layer of a QLED.
[0024] It should be noted that the above mechanism is merely speculation, and the present invention is not limited to the above mechanism.
[0025] Hereinafter, an embodiment of the present invention will be described. Note that the present invention is not limited to the following embodiment. In addition, the drawings are exaggerated for convenience of explanation, and the dimensional ratios of each component in each drawing may differ from the actual ratios. In addition, when the embodiment of the present invention is described with reference to the drawings, the same elements are given the same reference numerals in the description of the drawings, and duplicated explanations are omitted.
[0026] In this specification, unless otherwise specified, operations and measurements of physical properties are performed under conditions of room temperature (20° C. or higher and 25° C. or lower) and relative humidity of 40% RH or higher and 50% RH or lower.
[0027] In this specification, unless otherwise defined, "substituted" refers to being substituted with an alkyl group, a cycloalkyl group, a hydroxyalkyl group, an alkoxyalkyl group, an alkoxy group, a cycloalkoxy group, an alkenyl group, an alkynyl group, an amino group, an aryl group, an aryloxy group, an alkylthio group, a cycloalkylthio group, an arylthio group, an alkoxycarbonyl group, an aryloxycarbonyl group, a hydroxyl group (-OH), a carboxyl group (-COOH), a thiol group (-SH), or a cyano group (-CN). When a group is substituted, the form of substitution that is included in the definition before the substituted structure is further substituted is excluded. For example, when the substituent is an alkyl group, this alkyl group as a substituent is not further substituted with an alkyl group.
[0028] Here, the alkyl group as a substituent may be either linear or branched, and is preferably linear and having 1 to 20 carbon atoms, or branched and having 3 to 20 carbon atoms. Specific examples include methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, sec-butyl, tert-butyl, n-pentyl, isopentyl, tert-pentyl, neopentyl, 1,2-dimethylpropyl, n-hexyl, isohexyl, 1,3-dimethylbutyl, 1-isopropylpropyl, 1,2-dimethylbutyl, n-heptyl, 1,4-dimethylpentyl, 3-ethylpentyl, 2-methyl-1-isopropylpropyl, 1-ethyl-3 Examples of such groups include 3-methylbutyl, n-octyl, 2-ethylhexyl, 3-methyl-1-isopropylbutyl, 2-methyl-1-isopropyl, 1-tert-butyl-2-methylpropyl, n-nonyl, 3,5,5-trimethylhexyl, n-decyl, isodecyl, n-undecyl, 1-methyldecyl, n-dodecyl, n-tridecyl, n-tetradecyl, n-pentadecyl, n-hexadecyl, n-heptadecyl, n-octadecyl, nonadecyl, and icosyl groups.
[0029] Examples of the cycloalkyl group as a substituent include a cyclopropyl group, a cyclobutyl group, a cyclopentyl group, and a cyclohexyl group.
[0030] Examples of the hydroxyalkyl group as a substituent include the above-mentioned alkyl groups substituted with 1 to 3 (preferably 1 to 2, particularly preferably 1) hydroxyl groups (e.g., hydroxymethyl group, hydroxyethyl group).
[0031] Examples of the alkoxyalkyl group as a substituent include the above alkyl groups substituted with 1 to 3 (preferably 1 to 2, particularly preferably 1) of the above alkoxy groups.
[0032] The alkoxy group as a substituent may be either linear or branched, and preferably includes linear alkoxy groups having from 1 to 20 carbon atoms or branched alkoxy groups having from 3 to 20 carbon atoms. Examples include methoxy, ethoxy, propoxy, isopropoxy, butoxy, pentyloxy, hexyloxy, heptyloxy, octyloxy, nonyloxy, decyloxy, undecyloxy, dodecyloxy, tridecyloxy, tetradecyloxy, pentadecyloxy, hexadecyloxy, heptadecyloxy, octadecyloxy, 2-ethylhexyloxy, and 3-ethylpentyloxy groups.
[0033] Examples of the cycloalkoxy group as a substituent include a cyclopropyloxy group, a cyclobutyloxy group, a cyclopentyloxy group, and a cyclohexyloxy group.
[0034] Examples of alkenyl groups as substituents include vinyl groups, allyl groups, 1-propenyl groups, isopropenyl groups, 1-butenyl groups, 2-butenyl groups, 3-butenyl groups, 1-pentenyl groups, 2-pentenyl groups, 3-pentenyl groups, 1-hexenyl groups, 2-hexenyl groups, 3-hexenyl groups, 1-heptenyl groups, 2-heptenyl groups, 5-heptenyl groups, 1-octenyl groups, 3-octenyl groups, and 5-octenyl groups.
[0035] Examples of the alkynyl group as a substituent include an acetylenyl group, a 1-propynyl group, a 2-propynyl group, a 1-butynyl group, a 2-butynyl group, a 3-butynyl group, a 1-pentetyl group, a 2-pentetyl group, a 3-pentetyl group, a 1-hexynyl group, a 2-hexynyl group, a 3-hexynyl group, a 1-heptynyl group, a 2-heptynyl group, a 5-heptynyl group, a 1-octynyl group, a 3-octynyl group, and a 5-octynyl group.
[0036] The aryl group as the substituent includes an aryl group having a carbon number of 6 to 30. Examples thereof include a phenyl group, a naphthyl group, a biphenyl group, a fluorenyl group, anthryl group, a pyrenyl group, an azulenyl group, an acenaphthylenyl group, a terphenyl group, and a phenanthryl group.
[0037] Examples of the aryloxy group as a substituent include a phenoxy group and a naphthyloxy group.
[0038] Examples of the alkylthio group as a substituent include a methylthio group, an ethylthio group, a propylthio group, a pentylthio group, a hexylthio group, an octylthio group, and a dodecylthio group.
[0039] Examples of the cycloalkylthio group as a substituent include a cyclopentylthio group and a cyclohexylthio group.
[0040] Examples of the arylthio group as a substituent include a phenylthio group and a naphthylthio group.
[0041] Examples of the alkoxycarbonyl group as a substituent include a methyloxycarbonyl group, an ethyloxycarbonyl group, a butyloxycarbonyl group, an octyloxycarbonyl group, and a dodecyloxycarbonyl group.
[0042] Examples of the aryloxycarbonyl group as a substituent include a phenyloxycarbonyl group and a naphthyloxycarbonyl group.
[0043] [Copolymer] The copolymer of the present invention has a structural unit (structural unit (1)) represented by the following formula (1) or a structural unit (structural unit (2)) represented by the following formula (2). The copolymer having structural unit (1) or (2) has excellent exciton resistance and electron resistance, as well as high hole mobility. Therefore, an electroluminescent device (particularly a quantum dot electroluminescent device) having the copolymer of the present invention (particularly in the hole transport layer or hole injection layer) can achieve a good balance between luminous efficiency and durability (luminous life). In addition, high current efficiency and low driving voltage can be achieved. The copolymer of the present invention may contain one type of structural unit (structural unit (1)) of formula (1), or may contain two or more types of structural units (1). Note that the multiple structural units (1) may be present in a block form or random form. Similarly, the copolymer of the present invention may contain one type of structural unit (structural unit (2)) of formula (2), or may contain two or more types of structural units (2). The multiple structural units (2) may be present in a block form or a random form. Alternatively, the copolymer of the present invention may contain a combination of one or more structural units of formula (1) (structural unit (1)) and one or more structural units of formula (2) (structural unit (2)). In this case, the copolymer of the present invention may be any of a random copolymer, an alternating copolymer, a periodic copolymer, and a block copolymer. Preferably, the copolymer of the present invention has a structural unit of formula (1) (structural unit (1)).
[0044] [ka]
[0045] In the above formula (1) and formula (2), the structural unit X ("-Ar 1 The left-hand structural unit not containing "-" (hereinafter the same) constitutes the copolymer according to the present invention. When two or more kinds of structural units (1) or (2) are present, the "structural unit X" in each structural unit (1) or (2) may be the same or different. Similarly, "-Ar" in the above formula (1) or formula (2) 1The - structural unit constitutes the copolymer according to the present invention. When two or more types of structural units (1) or (2) are present, the "-Ar" in each structural unit (1) or (2) 1 -" may be the same or different.
[0046] In the above formula (1) and formula (2), R 1 represents a substituted or unsubstituted alkyl group having from 1 to 20 carbon atoms, a substituted or unsubstituted monovalent aromatic hydrocarbon group having from 6 to 30 ring carbon atoms, a substituted or unsubstituted monovalent aromatic heterocyclic group having from 5 to 30 ring atoms, or -YN(Ar 2 )(Ar 3). Examples of the alkyl group having 1 to 20 carbon atoms include the same alkyl groups as those listed in the "substituent" above. Among these, from the viewpoint of further improving exciton resistance, electron resistance, and hole mobility (hence further improving luminous efficiency and durability (luminous life)), the alkyl group is preferably a straight-chain or branched alkyl group having 1 to 8 carbon atoms, more preferably a branched alkyl group having 3 to 5 carbon atoms (isopropyl group, sec-butyl group, tert-butyl group, isopentyl group, neopentyl group), and particularly preferably a sec-butyl group. Furthermore, the monovalent aromatic hydrocarbon group having 6 to 30 ring carbon atoms is not particularly limited, but specific examples include monovalent groups derived from aromatic hydrocarbon compounds such as benzene (phenyl group), pentalene, indene, naphthalene, anthracene, azulene, heptalene, acenaphthene, phenalene, fluorene, phenanthroline, biphenyl, terphenyl, quaterphenyl, quinquiphenyl, pyrene, 9,9-diphenylfluorene, 9,9'-spirobi[fluorene], and 9,9-dialkylfluorene. The monovalent aromatic heterocyclic group having 5 to 30 ring atoms is not particularly limited, but specific examples thereof include monovalent groups derived from heterocyclic aromatic compounds such as acridine, phenazine, benzoquinoline, benzoisoquinoline, phenanthridine, phenanthroline, anthraquinone, fluorenone, dibenzofuran, dibenzothiophene, carbazole, imidazophenanthridine, benzimidazophenanthridine, azadibenzofuran, 9-phenylcarbazole, azacarbazole, azadibenzothiophene, diazadibenzofuran, diazacarbazole, diazadibenzothiophene, xanthone, thioxanthone, pyridine, quinoline, and anthraquinoline. 1 The (unsubstituted form) may be only the monovalent aromatic hydrocarbon group as described above, a structure in which two or more types of monovalent aromatic hydrocarbon groups as described above are combined, only the monovalent aromatic heterocyclic group as described above, a structure in which two or more types of monovalent aromatic heterocyclic groups as described above are combined, or a structure in which one or more types of monovalent aromatic hydrocarbon groups and one or more types of monovalent aromatic heterocyclic groups as described above are combined.1 -YN(Ar 2 )(Ar 3 In the above formula, Y represents a substituted or unsubstituted divalent aromatic hydrocarbon group having 6 to 30 ring carbon atoms. In this case, the divalent aromatic hydrocarbon group having 6 to 30 ring carbon atoms includes the above R 1 Examples of divalent groups derived from aromatic hydrocarbon compounds in the above are similar. Among these, from the viewpoint of further improving exciton resistance and electron resistance, and hole mobility (hence further improving luminous efficiency and durability (luminous life)), Y preferably represents a substituted or unsubstituted phenylene group, a substituted or unsubstituted fluorenylene group, a substituted or unsubstituted dibenzofuranylene group, a substituted or unsubstituted naphthylene group, or a substituted or unsubstituted dibenzothiophenyl group, more preferably a substituted or unsubstituted phenylene group (o-, m-, p-phenylene group), a substituted or unsubstituted fluorenylene group, or a substituted or unsubstituted dibenzofuranylene group, and even more preferably a phenylene group (particularly a p-phenylene group). In addition, Ar 2 and Ar 3 each independently represents a substituted or unsubstituted monovalent aromatic hydrocarbon group having 6 to 30 ring carbon atoms, or a substituted or unsubstituted monovalent aromatic heterocyclic group having 5 to 30 ring atoms. 2 and Ar 3 The monovalent aromatic hydrocarbon group having 6 to 30 ring carbon atoms and the monovalent aromatic heterocyclic group having 5 to 30 ring atoms include the above-mentioned R 1 Among these, from the viewpoint of exciton resistance, electron resistance, and further improvement of hole mobility (hence further improvement of luminous efficiency and durability (luminous life)), Ar 2 and Ar 3represents preferably a substituted or unsubstituted phenyl group, a substituted or unsubstituted fluorenyl group, a substituted or unsubstituted dibenzofuranyl group, a substituted or unsubstituted biphenyl group, a substituted or unsubstituted naphthylene group, or a substituted or unsubstituted spirobifluorenyl group, more preferably a substituted or unsubstituted phenyl group, a substituted or unsubstituted fluorenyl group, a substituted or unsubstituted dibenzofuranyl group, or a substituted or unsubstituted biphenyl group, and further preferably a substituted or unsubstituted fluorenyl group (particularly a fluorenyl group substituted with two alkyl groups having 1 to 3 carbon atoms (particularly methyl groups)) or a substituted or unsubstituted biphenyl group (particularly an unsubstituted biphenyl group).
[0047] In the above formula (1) or (2), from the viewpoint of further improving the exciton tolerance and electron tolerance, as well as the hole mobility (hence, further improving the luminous efficiency and durability (luminous lifetime)), R 1 is a substituted or unsubstituted alkyl group having 1 to 8 carbon atoms, or -YN(Ar 2 )(Ar 3 ) is preferably represented.
[0048] In the above formula (1) or (2), R 2 and R 3 each independently represents a substituted or unsubstituted alkyl group having from 1 to 20 carbon atoms, a substituted or unsubstituted alkoxy group having from 1 to 20 carbon atoms, a substituted or unsubstituted monovalent aromatic hydrocarbon group having from 6 to 30 ring carbon atoms, or a substituted or unsubstituted monovalent aromatic heterocyclic group having from 5 to 30 ring atoms. 2 and two R 3 may be the same or different from each other. 2 and two R 3may be bonded to each other to form a ring. Examples of the alkyl group having 1 to 20 carbon atoms and the alkoxy group having 1 to 20 carbon atoms are the same as those listed in the "substituent" above. Examples of the monovalent aromatic hydrocarbon group having 6 to 30 ring carbon atoms and the monovalent aromatic heterocyclic group having 5 to 30 ring atoms are the same as those listed in the "substituent" above. 1 Among these, from the viewpoint of exciton resistance, electron resistance, and further improvement of hole mobility (hence further improvement of luminous efficiency and durability (luminous life)), R 2 and R 3 each independently represents a substituted or unsubstituted alkyl group having 1 to 8 carbon atoms, a substituted or unsubstituted phenyl group, or two R 2 Or two R's 3 are preferably bonded to each other to form a ring; R 2 and R 3 each independently represents a substituted or unsubstituted alkyl group having 1 to 3 carbon atoms (particularly a methyl group) or an unsubstituted phenyl group, or more preferably, two phenyl groups are bonded to each other to form a fluorene ring; R 2 and R 3 It is particularly preferred that represents a phenyl group, and that these two phenyl groups are bonded to each other to form a fluorene ring.
[0049] In the above formula (1) or (2), X 1 and X 2 Each independently represents a carbon atom (C) or a silicon atom (Si). 1 and X 2 represents a carbon atom (C).
[0050] In a preferred embodiment of the present invention, the copolymer has a constitutional unit represented by the above formula (1). In a preferred embodiment of the present invention, the copolymer has a constitutional unit represented by the above formula (1), in which R 1is a substituted or unsubstituted alkyl group having 1 to 8 carbon atoms, or -YN(Ar 2 )(Ar 3 ), where Y represents a substituted or unsubstituted phenylene group, a substituted or unsubstituted fluorenylene group, or a substituted or unsubstituted dibenzofuranylene group; Ar 2 and Ar 3 each independently represents a substituted or unsubstituted phenyl group, a substituted or unsubstituted fluorenyl group, a substituted or unsubstituted dibenzofuranyl group, or a substituted or unsubstituted biphenyl group; R 2 each independently represents a substituted or unsubstituted alkyl group having 1 to 8 carbon atoms, a substituted or unsubstituted phenyl group, or R 2 may be bonded to each other to form a ring; X 1 represents a carbon atom (C).
[0051] In a more preferred embodiment of the present invention, the copolymer has a constitutional unit represented by the above formula (1), in which R 1 is a substituted or unsubstituted branched alkyl group having 3 to 5 carbon atoms (isopropyl group, sec-butyl group, tert-butyl group, isopentyl group, neopentyl group), or -YN(Ar 2 )(Ar 3 ), in which Y represents a substituted or unsubstituted phenylene group (o-, m-, p-phenylene group), a substituted or unsubstituted fluorenylene group, or a substituted or unsubstituted dibenzofuranylene group; Ar 2 and Ar 3 R each independently represents a substituted or unsubstituted fluorenyl group (particularly a fluorenyl group substituted with two alkyl groups having 1 to 3 carbon atoms (particularly a methyl group)) or a substituted or unsubstituted biphenyl group (particularly an unsubstituted biphenyl group); 2 represents a substituted or unsubstituted alkyl group having 1 to 3 carbon atoms (especially a methyl group) or an unsubstituted phenyl group, or two phenyl groups bonded together to form a fluorene ring; X 1represents a carbon atom (C).
[0052] That is, the structural unit X ("-Ar" in the above formula (1) or (2) 1 A preferred example of the left-hand structural unit not containing "-" is the following structure: A copolymer having the above structure can further improve exciton resistance, electron resistance, and hole mobility (hence, can further improve luminous efficiency and durability (luminous lifetime)).
[0053] [ka]
[0054] [ka]
[0055] [ka]
[0056] [ka]
[0057] [ka]
[0058] [ka]
[0059] [ka]
[0060] [ka]
[0061] [ka]
[0062] [ka]
[0063] [ka]
[0064] [ka]
[0065] The copolymer of the above formula (1) or (2) contains, in addition to the above structural unit X, "-Ar 1 When two or more types of structural units (1) or (2) are present, the "-Ar" in each structural unit (1) or (2) is 1 -" may be the same or different, where Ar 1 represents a substituted or unsubstituted divalent aromatic hydrocarbon group having 6 to 30 ring carbon atoms, or a substituted or unsubstituted divalent aromatic heterocyclic group having 5 to 30 ring atoms. The divalent aromatic hydrocarbon group having 6 to 30 ring carbon atoms and the divalent aromatic heterocyclic group having 5 to 30 ring atoms include the above-mentioned R 1 Among these, from the viewpoint of exciton resistance, electron resistance, and further improvement of hole mobility (hence further improvement of luminous efficiency and durability (luminous life)), Ar 1 is preferably a group selected from the following formulas (3) to (18).
[0066] [ka]
[0067] In the above formulas (3) to (18), R 4 each independently represents a hydrogen atom, an alkyl group having from 1 to 20 carbon atoms, a substituted or unsubstituted monovalent aromatic hydrocarbon group having from 6 to 30 ring carbon atoms, or a substituted or unsubstituted monovalent aromatic heterocyclic group having from 5 to 30 ring atoms. 4 If these R 4 may be the same or different. Examples of the alkyl group having 1 to 20 carbon atoms include the same alkyl groups as those listed in the "substituent" above. Examples of the monovalent aromatic hydrocarbon group having 6 to 30 ring carbon atoms and the monovalent aromatic heterocyclic group having 5 to 30 ring atoms include the above-mentioned R 1 Among these, from the viewpoint of exciton resistance, electron resistance, and further improvement of hole mobility (hence further improvement of luminous efficiency and durability (luminous life)), R 4 are each independently preferably a linear alkyl group having 3 to 20 carbon atoms, a branched alkyl group having 3 to 20 carbon atoms, or a hydrogen atom, and more preferably a linear alkyl group having 6 to 12 carbon atoms or a hydrogen atom.
[0068] In the above formulas (3) to (18), Q is each independently -O-, -S-, -Se-, -CR 5 R 6 -, -SiR 5 R 6 - represents Q. 5 R 6 -, -SiR 5 R 6 It is preferred that -CR 5 R 6 It is more preferred that Q represents -CR 5 R 6 - When expressing R 5 and R 6R each independently represents a hydrogen atom, a deuterium atom, a substituted or unsubstituted alkyl group having 1 to 20 carbon atoms, a substituted or unsubstituted aryl group, or a substituted or unsubstituted heteroaryl group. 5 and R 6 may be the same or different. Here, examples of the alkyl group and the aryl group include the same alkyl group and aryl group as those listed in the above "substituent". Examples of the heteroaryl group include, for example, a 1-pyrrolyl group, a 2-pyrrolyl group, a 3-pyrrolyl group, a pyrazinyl group, a 2-pyridinyl group, a 3-pyridinyl group, a 4-pyridinyl group, a 1-indolyl group, a 2-indolyl group, a 3-indolyl group, a 4-indolyl group, a 5-indolyl group, a 6-indolyl group, a 7-indolyl group, a 1-isoindolyl group, a 2-isoindolyl group, a 3-isoindolyl group, a 4-isoindolyl group, a 5-isoindolyl group, a 6-isoindolyl group, a 7-isoindolyl group, a 2-carbazolyl group, a 3-isoindolyl group, a 4-isoindolyl group, a 5-isoindolyl group, a 6-isoindolyl group, a 7-isoindolyl group, a 2-carbazolyl group, a 3-isoindolyl group, a 4-isoindolyl group, a 5-isoindolyl group, a 6-isoindolyl group, a 7-isoindolyl group, a 2-carbazolyl group, a 1-pyrrolyl group, a 2-pyrrolyl group, a 3-pyridinyl group, a 4-pyridin ... -carbazolyl group, 4-carbazolyl group, 9-carbazolyl group, 1-acridinyl group, 2-acridinyl group, 3-acridinyl group, 4-acridinyl group, 9-acridinyl group, 1-phenazinyl group, 2-phenazinyl group, 1-phenothiazinyl group, 2-phenothiazinyl group, 3-phenothiazinyl group, 4-phenothiazinyl group, 10-phenothiazinyl group, 1-phenoxazinyl group, 2-phenoxazinyl group, 3-phenoxazinyl group, 4-phenoxazinyl group, 10-phenoxazinyl group, etc. Among these, from the viewpoint of further improvement of exciton resistance and electron resistance, and hole mobility (hence further improvement of luminous efficiency and durability (luminous life)), R 5 and R 6 represents preferably a linear or branched alkyl group having 3 to 20 carbon atoms, more preferably a linear alkyl group having 6 to 12 carbon atoms, and particularly preferably a linear alkyl group having 7 to 9 carbon atoms.
[0069] In the above formulas (3) to (18), each Z is independently -CR 7 =, -N=, -SiR 7 = where R7 represents a hydrogen atom, a deuterium atom, a substituted or unsubstituted alkyl group having 1 to 20 carbon atoms, a substituted or unsubstituted aryl group, or a substituted or unsubstituted heteroaryl group. Here, examples of the alkyl group and the aryl group include the same alkyl groups and aryl groups as those listed in the above "substituents". In addition, examples of the heteroaryl group include the above R 5 and R 6 Examples of the heteroaryl groups are the same as those listed in the above.
[0070] In the above formulas (3) to (18), * represents a bonding site that forms the main chain.
[0071] Of the above, Ar 1 is preferably a group represented by formula (3), formula (4), formula (5), or formula (13), more preferably R 4 are each independently a linear alkyl group having 3 to 20 carbon atoms, a branched alkyl group having 3 to 20 carbon atoms, or a hydrogen atom; or Q is -CR 5 R 6 In this case, R 5 and R 6 are each independently a linear or branched alkyl group having 3 to 20 carbon atoms, and more preferably R 4 are each independently a linear alkyl group having 6 to 12 carbon atoms or a hydrogen atom, or Q is -CR 5 R 6 In this case, R 5 and R 6 are each independently a linear alkyl group having 6 to 12 carbon atoms, and particularly preferably Q is -CR 5 R 6 In this case, R 5 and R 6 are each independently a linear alkyl group having 7 to 9 carbon atoms, represented by formula (5).
[0072] The composition of the structural unit (1) or (2) in the copolymer according to the present invention is not particularly limited. Considering the exciton resistance and electron resistance, and further improvement of hole mobility by the copolymer (hence further improvement of luminous efficiency and durability (luminous life)), the structural unit (1) or (2) is preferably 85 mol% or more and 100 mol% or less, more preferably more than 90 mol% and 100 mol% or less, and particularly preferably 100 mol% with respect to all structural units constituting the copolymer (the copolymer according to the present invention is composed only of the structural unit (1) or (2)). In addition, when the copolymer contains two or more kinds of structural units (1) or (2), the content of the structural unit (1) or (2) means the total amount of the structural unit (1) or (2). In addition, when the copolymer contains both the structural units (1) and (2), the content means the total amount of the structural units (1) and (2).
[0073] The copolymer according to the present invention essentially contains the structural unit (1) or (2), but may have other structural units in addition to these structural units (1) or (2). Here, examples of the other structural units include structural units derived from compounds such as azulene, naphthalene, anthracene, terphenylene, and phenanthrene. Here, when the copolymer according to the present invention has other structural units, the composition of the other structural units is not particularly limited. Considering the exciton resistance and electron resistance, as well as further improvement of hole mobility (hence further improvement of luminous efficiency and durability (luminous life)), the other structural units are preferably more than 0 mol% and less than 15 mol%, more preferably 0.5 mol% or more and 10 mol% or less, based on the total structural units constituting the copolymer. In addition, when the copolymer contains two or more kinds of other structural units, the content of the other structural units means the total amount of the other structural units.
[0074] The weight average molecular weight (Mw) of the copolymer according to the present invention is not particularly limited as long as the objective effect of the present invention is obtained. The weight average molecular weight (Mw) is, for example, preferably 2,000 to 500,000, more preferably 5,000 to 200,000. With such a weight average molecular weight, it is possible to form a layer with a uniform thickness by appropriately adjusting the viscosity of the coating solution for forming a layer (e.g., a hole injection layer, a hole transport layer) using the copolymer.
[0075] The number average molecular weight (Mn) of the copolymer is not particularly limited as long as the objective effect of the present invention is obtained. The number average molecular weight (Mn) is, for example, preferably 1,000 to 200,000, more preferably 2,500 to 100,000. With such a number average molecular weight, it is possible to form a layer with a uniform thickness by appropriately adjusting the viscosity of a coating solution for forming a layer (e.g., a hole injection layer, a hole transport layer) using the copolymer. The polydispersity (weight average molecular weight / number average molecular weight) of the copolymer of this embodiment is, for example, 1.10 to 5.00, preferably 1.20 to 2.00.
[0076] Here, the number average molecular weight (Mn) and weight average molecular weight (Mw) are not particularly limited in measurement, and may be measured by a known method or by appropriately modifying a known method. In this specification, the number average molecular weight (Mn) and weight average molecular weight (Mw) are values measured by the following method. The polydispersity (Mw / Mn) of a polymer is calculated by dividing the weight average molecular weight (Mw) by the number average molecular weight (Mn) measured by the following method.
[0077] (Measurement of number average molecular weight (Mn) and weight average molecular weight (Mw)) The number average molecular weight (Mn) and weight average molecular weight (Mw) of a copolymer (in the following case, a polymeric material) are measured by SEC (Size Exclusion Chromatography) using polystyrene as a standard under the following conditions:
[0078] (SEC measurement conditions) Analytical equipment (SEC): Shimadzu Corporation, Prominence Column: Polymer Laboratories, PLgel MIXED-B Column temperature: 40℃ Flow rate: 1.0mL / min Amount of sample solution injected: 20 μL (polymer concentration: approximately 0.05% by mass) Eluent: tetrahydrofuran (THF) Detector (UV-VIS detector): Shimadzu Corporation, SPD-10AV Standard sample: polystyrene.
[0079] The terminal of the main chain of the copolymer according to this embodiment is not particularly limited and is appropriately determined depending on the type of raw material used, but is usually a hydrogen atom.
[0080] The copolymer according to this embodiment can be synthesized by using a known organic synthesis method. A specific synthesis method of the copolymer according to this embodiment can be easily understood by a person skilled in the art by referring to the examples described below. For example, when the copolymer has a structural unit of the above formula (1), the copolymer according to this embodiment can be produced by a polymerization reaction using one or more monomers (A-1) represented by the following formula (A-1), or by a copolymerization reaction using one or more monomers (A-1) represented by the following formula (A-1) and other monomers corresponding to the above other structural units.
[0081] [ka]
[0082] Alternatively, it can be produced by a copolymerization reaction using one or more monomers (A-2) represented by the following formula (A-2) and one or more monomers (A-3) represented by the following formula (A-3), or using one or more monomers (A-2) represented by the following formula (A-2), one or more monomers (A-3) represented by the following formula (A-3), and other monomers corresponding to the other structural units described above.
[0083] [ka]
[0084] [ka]
[0085] For example, when the copolymer has a structural unit of the above formula (2), the copolymer according to this embodiment can be produced by a polymerization reaction using one or more monomers (B-1) represented by the following formula (B-1), or by a copolymerization reaction using one or more monomers (B-1) represented by the following formula (B-1) and other monomers corresponding to the other structural units.
[0086] [ka]
[0087] Alternatively, it can be produced by a copolymerization reaction using one or more monomers (B-2) represented by the following formula (B-2) and one or more monomers (B-3) represented by the following formula (B-3), or using one or more monomers (B-2) represented by the following formula (B-2), one or more monomers (B-3) represented by the following formula (B-3), and other monomers corresponding to the other structural units described above.
[0088] [ka]
[0089] [ka]
[0090] The above-mentioned monomers used in the polymerization of the copolymer according to the present invention can be synthesized by appropriately combining known synthesis reactions, and their structures can be confirmed by known methods (for example, NMR, LC-MS, etc.).
[0091] In the above formulas (A-1) to (A-3), R 1 , R 2 , X 1 and Ar 1 is defined as in the above formula (1). Similarly, in the above formulas (B-1) to (B-3), R 1 , R 2 , R 3 , X 1 , X 2 and Ar 1 is defined as in the above formula (2). 1 , Z 1’ , Z 1” , Z 2 , Z 2’ and Z 2” are each independently a halogen atom (a fluorine atom, a chlorine atom, a bromine atom, an iodine atom, particularly a bromine atom) or a group having the following structure. In the following structure, R A ~R D are each independently an alkyl group having 1 to 3 carbon atoms. A ~R D is a methyl group. In addition, Z in the above formulae (A-1) to (A-3) and (B-1) to (B-3) 1 and Z 2 , Z 1’ and Z 2’ , or Z 1” and Z 2” may be the same or different. Preferably, in the above formula (A-1) or (B-1), Z 1 and Z 2 In the above formula (A-2) or (B-2), Z 1’ and Z 2’In the above formula (A-3) or (B-3), Z 1” and Z 2” are the same and Z 1’ and Z 2’ It is preferable that it is different from.
[0092] [ka]
[0093] The copolymer having the structural unit (1) or the structural unit (2) (preferably the structural unit (1)) has a high bond dissociation energy of the C-N bond (excellent exciton resistance and electron resistance) and a narrow dihedral angle of the C-N bond axis (high hole mobility). Therefore, when the copolymer according to this embodiment is used as a hole injection material or a hole transport material (particularly a hole transport material), high luminous efficiency and excellent durability (luminous lifetime) can be achieved in a well-balanced manner. In addition, the copolymer according to this embodiment has a high triplet energy level and a low driving voltage. Therefore, when the copolymer according to this embodiment is used as a hole injection material or a hole transport material (particularly a hole transport material), high hole mobility is achieved at a low driving voltage. Therefore, an electroluminescent device (particularly a QLED) using the copolymer according to this embodiment has excellent luminous efficiency and durability (luminous lifetime).
[0094] [Electroluminescence device materials] The copolymer according to this embodiment is preferably used as an electroluminescence device material. According to this embodiment, an electroluminescence device material having excellent luminous efficiency and durability (luminescence life) is provided. In addition, the copolymer according to this embodiment also provides an electroluminescence device material having a high triplet energy level (current efficiency) and a low driving voltage. Furthermore, the copolymer according to this embodiment exhibits high solubility in a solvent and high heat resistance. Therefore, it can be easily formed into a film (thin film) by a wet (coating) method. Therefore, in a second aspect of the present invention, an electroluminescence device material containing the copolymer according to this embodiment is provided. Alternatively, the use of the copolymer according to the present invention as an electroluminescence device material is provided.
[0095] [Electroluminescent element] As described above, the copolymer according to the present embodiment is preferably used in an electroluminescence element. That is, an electroluminescence element is provided that includes a pair of electrodes and one or more organic films disposed between the electrodes and containing the copolymer according to the present embodiment or an electroluminescence element material. Such an electroluminescence element can achieve a good balance between high luminous efficiency (particularly excellent luminous efficiency at a low driving voltage) and excellent durability (luminescence life). Therefore, in a third aspect, the present invention provides an electroluminescence element that includes a first electrode, a second electrode, and one or more organic films disposed between the first electrode and the second electrode, at least one layer of the organic film containing the copolymer according to the present embodiment. The object (or effect) of the present invention can also be achieved by such an electroluminescence element according to the present embodiment. As a preferred embodiment of the above aspect, the electroluminescence element further includes a light-emitting layer disposed between the electrodes and containing a light-emitting material capable of emitting light from triplet excitons. The electroluminescence element according to the present embodiment is an example of an electroluminescence element according to the present invention.
[0096] Furthermore, the present embodiment provides a method for producing an electroluminescence element including a pair of electrodes and one or more organic films disposed between the electrodes and containing the copolymer of the present embodiment, in which at least one of the organic films is formed by a coating method. The present embodiment also provides an electroluminescence element in which at least one of the organic films is formed by a coating method using this method.
[0097] The copolymer of this embodiment and the electroluminescence device material (EL device material) of this embodiment (hereinafter collectively referred to as "copolymer / EL device material") have excellent solubility in organic solvents. Therefore, the copolymer / EL device material of this embodiment is particularly suitable for use in the manufacture of devices (particularly thin films) by a coating method (wet process). For this reason, this embodiment provides a liquid composition containing the copolymer of this embodiment and a solvent or dispersion medium. Such a liquid composition is one example of the liquid composition according to the present invention.
[0098] In addition, the electroluminescent device material according to the embodiment as described above is preferably used for manufacturing a device (particularly a thin film) by a coating method (wet process). From the above viewpoint, the present embodiment provides a thin film containing the copolymer of the present embodiment. Such a thin film is an example of the thin film according to the present invention.
[0099] In addition, the EL element material according to the present embodiment has excellent hole injection properties and hole mobility. Therefore, it can be suitably used in the formation of any organic film such as a hole injection material, a hole transport material, or a light-emitting material (host). Among these, from the viewpoint of hole transport properties, it is suitably used as a hole injection material or a hole transport material, and is particularly suitably used as a hole transport material.
[0100] That is, the present embodiment provides a composition containing a copolymer and at least one material selected from the group consisting of a hole transport material, an electron transport material, and a light emitting material. The light emitting material contained in the composition is not particularly limited, but may contain an organometallic complex (a light emitting organometallic complex compound) or a semiconductor nanoparticle (a semiconductor inorganic nanoparticle).
[0101] The electroluminescent element according to the present embodiment will be described in detail below with reference to Fig. 1. Fig. 1 is a schematic diagram showing the electroluminescent element according to the present embodiment. In this specification, the "electroluminescent element" may be abbreviated to "EL element".
[0102] As shown in FIG. 1, the EL element 100 according to this embodiment includes a substrate 110, a first electrode 120 disposed on the substrate 110, a hole injection layer 130 disposed on the first electrode 120, a hole transport layer 140 disposed on the hole injection layer 130, an emitting layer 150 disposed on the hole transport layer 140, an electron transport layer 160 disposed on the emitting layer 150, an electron injection layer 170 disposed on the electron transport layer 160, and a second electrode 180 disposed on the electron injection layer 170.
[0103] Here, the copolymer / EL element material of this embodiment is, for example, contained in any of the organic films (organic layers) arranged between the first electrode 120 and the second electrode 180. Specifically, the copolymer / EL element material is preferably contained in the hole injection layer 130 as a hole injection material, the hole transport layer 140 as a hole transport material, or the light emitting layer 150 as a light emitting material (host). It is more preferable that the copolymer / EL element material is contained in the hole injection layer 130 as a hole injection material or in the hole transport layer 140 as a hole transport material. It is particularly preferable that the copolymer / EL element material is contained in the hole transport layer 140 as a hole transport material. That is, in a preferred embodiment of the present invention, the organic film containing the copolymer / EL element material is a hole transport layer, a hole injection layer, or a light emitting layer. In a more preferred embodiment of the present invention, the organic film containing the copolymer is a hole transport layer or a hole injection layer. In a particularly preferred embodiment of the present invention, the organic film containing the copolymer is a hole transport layer.
[0104] The organic film containing the copolymer / EL element material of this embodiment is formed by a coating method (solution coating method). Specifically, the organic film is formed by a solution coating method such as a spin coat method, a casting method, a micro gravure coat method, a gravure coat method, a bar coat method, a roll coat method, a wire bar coat method, a dip coat method, a spray coat method, a screen printing method, a flexographic printing method, an offset printing method, or an ink jet printing method.
[0105] In addition, the solvent used in the solution coating method can be any solvent that can dissolve the copolymer / EL element material, and can be appropriately selected depending on the type of copolymer used. For example, toluene, xylene, ethylbenzene, diethylbenzene, methylene, propylbenzene, cyclohexylbenzene, dimethoxybenzene, anisole, ethoxytoluene, phenoxytoluene, isopropylbiphenyl, dimethylanisole, phenyl acetate, phenyl propionate, methyl benzoate, ethyl benzoate, cyclohexane, etc. are exemplified. In addition, the amount of the solvent used is not particularly limited, but considering the ease of coating, etc., it is an amount such that the concentration of the copolymer is preferably about 0.1% by mass or more and 10% by mass or less, more preferably about 0.5% by mass or more and 5% by mass or less.
[0106] The method for forming the layer other than the organic film containing the copolymer / EL element material is not particularly limited. The layer other than the organic film containing the copolymer / EL element material of the present embodiment may be formed by, for example, a vacuum deposition method or a solution coating method.
[0107] A substrate used in a general EL device can be used as the substrate 110. For example, the substrate 110 may be a glass substrate, a semiconductor substrate such as a silicon substrate, or a transparent plastic substrate.
[0108] A first electrode 120 is formed on the substrate 110. Specifically, the first electrode 120 is an anode, and is made of a metal, an alloy, a conductive compound, or the like that has a large work function. For example, the first electrode 120 is made of indium tin oxide (InO 2 ), which has excellent transparency and conductivity. 2 O 3 -SnO 2 :ITO), indium zinc oxide (In 2 O 3 -ZnO), Tin Oxide (SnO 2The first electrode 120 may be formed as a transmissive electrode using zinc oxide (ZnO) or the like. The first electrode 120 may be formed as a reflective electrode by laminating magnesium (Mg), aluminum (Al) or the like on the transparent conductive film. After the first electrode 120 is formed on the substrate 110, cleaning and UV-ozone treatment may be performed, if necessary.
[0109] A hole injection layer 130 is formed on the first electrode 120. The hole injection layer 130 is a layer that facilitates the injection of holes from the first electrode 120, and may be formed to a thickness of about 10 nm to about 1000 nm, more specifically, about 20 nm to about 50 nm (dry film thickness; the same applies below).
[0110] The hole injection layer 130 can be formed of a known hole injection material. Examples of known hole injection materials for forming the hole injection layer 130 include poly(ether ketone)-containg triphenylamine (TPAPEK), 4-isopropyl-4'-methyldiphenyliodonium tetrakis(pentafluorophenyl)borate (PPBI), N,N'-diphenyl-N,N'-bis-[4-(phenyl-m-tolyl-amino)-phenyl]-biphenyl-4,4'-diamine (DNTPD), copper phthalocyanine (CuPc), and the like. phthalocyanine), 4,4',4”-tris(3-methylphenylphenylamino)triphenylamine (m-MTDATA), N,N'-di(1-naphthyl)-N,N'-diphenylbenzidine (NPB), 4,4',4”-tris(diphenylamino)triphenylamine (TDATA), 4,4',4”-tris(N,N-2-naphthylphenylamino)triphenylamine (2-TNATA), polyaniline / dodecylbenzenesulphonic acid acid), poly(3,4-ethylenedioxythiophene) / poly(4-styrenesulfonate) (poly(3,Examples of such a polymer include 4-ethylenedioxythiophene / poly(4-styrenesulfonate):PEDOT / PSS, and polyaniline / 10-camphorsulfonic acid.
[0111] The hole transport layer 140 is formed on the hole injection layer 130. The hole transport layer 140 is a layer having a function of transporting holes, and may be formed to a thickness of, for example, about 10 nm to about 150 nm, more specifically, about 20 nm to about 50 nm. The hole transport layer 140 is preferably formed by a solution coating method using the copolymer of this embodiment. This method can extend the durability (light emission life) of the EL element 100. It is also possible to improve the performance (light emission efficiency) of the EL element 100. It is also possible to improve the current efficiency of the EL element 100 and reduce the driving voltage. In addition, since the hole transport layer can be formed by the solution coating method, it can be efficiently formed in a large area.
[0112] However, when any other organic film of the EL element 100 contains the copolymer according to this embodiment, the hole transport layer 140 may be formed of a known hole transport material. Examples of known hole transport materials include 1,1-bis[(di-4-tolylamino)phenyl]cyclohexane (TAPC), carbazole derivatives such as N-phenylcarbazole and polyvinylcarbazole, N,N'-bis(3-methylphenyl)-N,N'-diphenyl-[1,1-biphenyl]-4,4'-diamine (N ,N'-bis(3-methylphenyl)-N,N'-diphenyl-[1,1-biphenyl]-4,4'-diamine (TPD), 4,4',4"-tris(N-carbazolyl)triphenylamine (TCTA), and N,N'-di(1-naphthyl)-N,N'-diphenylbenzidine (NPB).
[0113] The light-emitting layer 150 is formed on the hole transport layer 140. The light-emitting layer 150 is a layer that emits light by fluorescence, phosphorescence, or the like, and is formed by using a vacuum deposition method, a spin coating method, an inkjet printing method, or the like. The light-emitting layer 150 may be formed to a thickness of, for example, about 10 nm or more and about 60 nm or less, more specifically, about 20 nm or more and about 50 nm or less. As the light-emitting material of the light-emitting layer 150, a known light-emitting material can be used. However, the light-emitting material contained in the light-emitting layer 150 is preferably a light-emitting material that can emit light from triplet excitons (i.e., phosphorescence emission). In such a case, the driving life of the EL element 100 can be further improved.
[0114] The light-emitting layer 150 is not particularly limited and may have a known configuration. Preferably, the light-emitting layer contains semiconductor nanoparticles or an organometallic complex. That is, in a preferred embodiment of the present invention, the organic film has a light-emitting layer containing semiconductor nanoparticles or an organometallic complex. When the light-emitting layer contains semiconductor nanoparticles, the EL element is a quantum dot electroluminescent element (QLED), a quantum dot light-emitting element, or a quantum dot light-emitting element. When the light-emitting layer contains an organometallic complex, the EL element is an organic electroluminescent element (OLED).
[0115] In the case of a configuration (QLED) in which the light-emitting layer contains semiconductor nanoparticles, the light-emitting layer is a single layer or multiple layers of a large number of semiconductor nanoparticles (quantum dots). Here, the semiconductor nanoparticles (quantum dots) are particles of a certain size that have a quantum confinement effect. The diameter of the semiconductor nanoparticles (quantum dots) is not particularly limited, but is about 1 nm or more and 10 nm or less.
[0116] The semiconductor nanoparticles (quantum dots) arranged in the light-emitting layer can be synthesized by a wet chemical process, a metal organic chemical vapor deposition process, a molecular beam epitaxy process, or other similar processes, etc. Among them, the wet chemical process is a method in which a precursor material is put into an organic solvent to grow particles.
[0117] In the wet chemical process, the organic solvent naturally coordinates with the surface of the quantum dot crystals as the crystals grow, and acts as a dispersant to regulate the growth of the crystals. Therefore, the wet chemical process can control the growth of semiconductor nanoparticles more easily and at lower cost than gas phase deposition methods such as Metal Organic Chemical Vapor Deposition (MOCVD) and Molecular Beam Epitaxy (MBE).
[0118] By adjusting the size of semiconductor nanoparticles (quantum dots), the energy band gap can be adjusted, and light of various wavelengths can be obtained in the light-emitting layer (quantum dot light-emitting layer). Therefore, by using multiple quantum dots of different sizes, it is possible to realize a display that emits (or emits) light of multiple wavelengths. The size of the quantum dots can be selected to emit red, green, and blue light so that a color display can be constructed. The sizes of the quantum dots can also be combined to emit various color lights to emit white light.
[0119] As the semiconductor nanoparticles (quantum dots), a semiconductor material selected from the group consisting of II-VI group semiconductor compounds; III-V group semiconductor compounds; IV-VI group semiconductor compounds; IV group elements or compounds; and combinations thereof can be used.
[0120] The II-VI semiconductor compound is not particularly limited, but may be selected from the group consisting of two-element compounds selected from the group consisting of CdSe, CdTe, ZnS, ZnSe, ZnTe, ZnO, HgS, HgSe, HgTe, and mixtures thereof; three-element compounds selected from the group consisting of CdSeS, CdSeTe, CdSTe, ZnSeS, ZnTeSe, ZnSTe, HgSeS, HgSeTe, HgSTe, CdZnS, CdZnSe, CdZnTe, CdHgS, CdHgSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, and mixtures thereof; and four-element compounds selected from the group consisting of CdZnSeS, CdZnSeTe, CdZnSTe, CdHgSeS, CdHgSeTe, CdHgSTe, HgZnSeS, HgZnSeTe, HgZnSTe, and mixtures thereof.
[0121] The III-V semiconductor compound is not particularly limited, but may be selected from the group consisting of two-element compounds selected from the group consisting of GaN, GaP, GaAs, GaSb, AlN, AlP, AlAs, AlSb, InN, InP, InAs, InSb, and mixtures thereof; three-element compounds selected from the group consisting of GaNP, GaNAs, GaNSb, GaPAs, GaPSb, AlNP, AlNAs, AlNSb, AlPAs, AlPSb, InNP, InNAs, InNSb, InPAs, InPSb, GaAlNP, and mixtures thereof; and four-element compounds selected from the group consisting of GaAlNAs, GaAlNSb, GaAlPAs, GaAlPSb, GaInNP, GaInNAs, GaInNSb, GaInPAs, GaInPSb, InAlNP, InAlNAs, InAlNSb, InAlPAs, InAlPSb, and mixtures thereof.
[0122] The IV-VI semiconductor compound is not particularly limited, and may be selected from the group consisting of binary compounds selected from the group consisting of SnS, SnSe, SnTe, PbS, PbSe, PbTe, and mixtures thereof; ternary compounds selected from the group consisting of SnSeS, SnSeTe, SnSTe, PbSeS, PbSeTe, PbSTe, SnPbS, SnPbSe, SnPbTe, and mixtures thereof; and quaternary compounds selected from the group consisting of SnPbSSe, SnPbSeTe, SnPbSTe, and mixtures thereof.
[0123] The Group IV element or compound is not particularly limited, but may be selected from the group consisting of mono-element compounds selected from the group consisting of Si, Ge, and mixtures thereof; and bi-element compounds selected from the group consisting of SiC, SiGe, and mixtures thereof.
[0124] Semiconductor nanoparticles (quantum dots) can have a homogeneous single structure or a core-shell double structure. The core and shell can contain different materials. The materials constituting each core and shell can be made of different semiconductor compounds. However, the energy band gap of the shell material is larger than that of the core material. Specifically, structures such as ZnTeSe / ZnSe / ZnS, InP / ZnSe / ZnS, CdSe / ZnS, and InP / ZnS are preferred.
[0125] For example, we will explain how to fabricate quantum dots with a core (CdSe)-shell (ZnS) structure. First, we add (CH 3 ) 2 Precursors for the core (CdSe), such as Cd(dimethylcadmium) and TOPSe(trioctylphosphine selenide), are injected to generate crystals. At this time, the crystals are maintained at high temperature for a certain time so that they grow to a certain size, and then the precursor for the shell (ZnS) is injected to form a shell on the surface of the already generated core. This allows the creation of CdSe / ZnS quantum dots capped with TOPO.
[0126] In the case of an OLED in which the light-emitting layer includes an organic metal complex, the light-emitting layer 150 may include, as a host material, for example, 6,9-diphenyl-9'-(5'-phenyl-[1,1':3',1"-terphenyl]-3-yl)3,3'-bi[9H-carbazole], 3,9-diphenyl-5-(3-(4-phenyl-6-(5'-phenyl-[1,1':3',1"-terphenyl]-3-yl)-1,3,5,-triazine-2-yl )phenyl)-9H-carbazole, 9,9'-diphenyl-3,3'-bi[9H-carbazole], tris(8-quinolinato)aluminium (Alq3), 4,4'-bis(carbazol-9-yl)biphenyl (CBP), poly(n-vinyl carbazole) carbazole (PVK), 9,10-di(naphthalene)anthracene (ADN), 4,4',4”-tris(N-carbazolyl)triphenylamine (TCTA), 1,3,5-tris(N-phenyl-benzimidazol-2-yl)benzene (1,3,5-tris(N-phenyl-benzimidazol-2-yl)benzene (1,3,5-tris(N-phenyl-benzimidazol-2-yl)benzene) 3-tert-butyl-9,10-di(naphth-2-yl)anthracene (TPBI), 3-tert-butyl-9,10-di(naphth-2-yl)anthracene (TBADN), distyrylarylene (DSA), 4,4'-bis(9-carbazole)2,2'-dimethyl-biphenyl (dmCBP), and the like.
[0127] The light-emitting layer 150 may contain, as a dopant material, for example, perylene and its derivatives, rubrene and its derivatives, coumarin and its derivatives, 4-dicyanomethylene-2-(pdimethylaminostyryl)-6-methyl-4H-pyran (DCM) and its derivatives, bis[2-(4,6-difluorophenyl)pyridinate]picolinate iridium(III):FIrpic, bis(1-phenylisoquinoline)(acetylacetonate)iridium(III):Ir(piq), 2 (acac)), tris(2-phenylpyridine)iridium(III):Ir(ppy) 3 ), iridium (Ir) complexes such as tris(2-(3-p-oxyyl)phenyl)pyridineiridium(III), osmium (Os) complexes, platinum complexes, etc. Of these, it is preferable that the light-emitting material is a light-emitting organometallic complex compound.
[0128] The method for forming the light-emitting layer is not particularly limited. It can be formed by applying a coating solution containing semiconductor nanoparticles or an organometallic complex (solution coating method). In this case, it is preferable to select a solvent that does not dissolve the material in the hole transport layer (hole transport material, especially copolymer) as the solvent constituting the coating solution.
[0129] An electron transport layer 160 is formed on the light emitting layer 150. The electron transport layer 160 is a layer having a function of transporting electrons, and is formed by using a vacuum deposition method, a spin coating method, an ink jet method, or the like. The electron transport layer 160 may be formed to a thickness of, for example, about 15 nm or more and about 50 nm or less.
[0130] The electron transport layer 160 may be formed of a known electron transport material. Examples of known electron transport materials include (8-quinolinolato) lithium (lithium quinolate) (Liq), tris(8-quinolinolato)aluminum (Alq), and the like. 3 ), and compounds having a nitrogen-containing aromatic ring. Specific examples of the compound having a nitrogen-containing aromatic ring include a compound having a pyridine ring such as 1,3,5-tri[(3-pyridyl)-phen-3-yl]benzene, a compound having a triazine ring such as 2,4,6-tris(3'-(pyridin-3-yl)biphenyl-3-yl)-1,3,5-triazine, and a compound having a 2-(4-(N-phenylbenzoyl)phenyl)-1,3,5-triazine. Examples of the electron transport material include compounds containing an imidazole ring such as 2-(4-(N-phenylbenzoimidazolyl-1-yl-phenyl)-9,10-dinaphthylanthracene and 1,3,5-tris(N-phenyl-benzimidazol-2-yl)benzene (TPBI). The above electron transport materials may be used alone or as a mixture of two or more kinds.
[0131] An electron injection layer 170 is formed on the electron transport layer 160. The electron injection layer 170 is a layer having a function of facilitating the injection of electrons from the second electrode 180. The electron injection layer 170 is formed by using a vacuum deposition method or the like. The electron injection layer 170 may be formed to a thickness of about 0.1 nm to about 5 nm, more specifically, about 0.3 nm to about 2 nm. Any known material can be used to form the electron injection layer 170. For example, the electron injection layer 170 can be formed using a lithium compound such as (8-quinolinato)lithium (Liq) and lithium fluoride (LiF), sodium chloride (NaCl), cesium fluoride (CsF), lithium oxide (Li 2 O), barium oxide (BaO), or the like.
[0132] The second electrode 180 is formed on the electron injection layer 170. The second electrode 180 is formed by using a vacuum deposition method or the like. The second electrode 180 is specifically a cathode, and is formed of a metal, an alloy, a conductive compound, or the like that has a small work function. For example, the second electrode 180 may be formed as a reflective electrode using a metal such as lithium (Li), magnesium (Mg), aluminum (Al), or calcium (Ca), or an alloy such as aluminum-lithium (Al-Li), magnesium-indium (Mg-In), or magnesium-silver (Mg-Ag). The second electrode 180 may be formed to a thickness of about 10 nm to about 200 nm, more specifically, about 50 nm to about 150 nm. Alternatively, the second electrode 180 may be formed of a thin film of 20 nm or less of the above metal materials, indium tin oxide (In 2 O 3 -SnO 2 ) and indium zinc oxide (In 2 O 3 Alternatively, the electrode may be formed as a transparent electrode using a transparent conductive film such as ZnO.
[0133] The EL element 100 according to this embodiment has been described above as an example of an electroluminescence element according to the present invention. The EL element 100 according to this embodiment can further improve durability (light-emitting life) by providing an organic film (particularly a hole transport layer or a hole injection layer) containing a copolymer. In addition, the light-emitting efficiency (current efficiency) can be further improved and the driving voltage can be reduced.
[0134] The laminated structure of the EL element 100 according to the present embodiment is not limited to the above example. The EL element 100 according to the present embodiment may be formed with other known laminated structures. For example, the EL element 100 may omit one or more layers among the hole injection layer 130, the hole transport layer 140, the electron transport layer 160, and the electron injection layer 170, or may additionally include other layers. Each layer of the EL element 100 may be formed as a single layer or as a multiple layer structure.
[0135] For example, the EL device 100 may further include a hole blocking layer between the hole transport layer 140 and the light emitting layer 150 in order to prevent excitons or holes from diffusing into the electron transport layer 160. The hole blocking layer may be formed of, for example, an oxadiazole derivative, a triazole derivative, or a phenanthroline derivative.
[0136] Furthermore, the copolymer according to the present embodiment can be applied to electroluminescence elements other than the above-mentioned QLED or OLED. The other electroluminescence elements to which the copolymer according to the present embodiment can be applied include, but are not limited to, organic-inorganic perovskite light-emitting elements, for example. EXAMPLES
[0137] The effects of the present invention will be described using the following examples and comparative examples. However, the technical scope of the present invention is not limited to the following examples. In the following examples, unless otherwise specified, the operations were performed at room temperature (25°C). Furthermore, unless otherwise specified, "%" and "parts" mean "% by mass" and "parts by mass", respectively.
[0138] Synthesis Example 1 (Synthesis of Compound 1) Compound 1 was synthesized according to the following reaction.
[0139] [ka]
[0140] Into an argon-purged three-neck flask, 3,6-dichlorocarbazole (35.00 g), 1-bromo-2-iodobenzene (210.00 g), copper iodide (30 g), and potassium carbonate (38.00 g) were placed and heated and stirred at 180°C for 3 days. Toluene was added to the reaction solution cooled to room temperature (25°C), and insoluble matter was filtered off. The eluate was distilled off under reduced pressure, and the residue was recrystallized from toluene and ethanol to obtain compound 1 (40.52 g).
[0141] Synthesis Example 2 (Synthesis of compound 2) Compound 2 was synthesized according to the following reaction.
[0142] [ka]
[0143] In a three-neck flask substituted with argon, compound 1 (20.00 g) obtained in the above Synthesis Example 1 and 200 ml of dehydrated tetrahydrofuran (THF) were placed and stirred at -48°C for 10 minutes. Then, 20 ml of a 2.8 M hexane solution of n-butyllithium (n-BuLi) was dropped, and after stirring at -48°C for 30 minutes, fluorenone (20.00 g) dissolved in 20 ml of dehydrated tetrahydrofuran was dropped and stirred at room temperature for 1 hour. Then, water was added to the reaction solution, and the mixture was extracted with ethyl acetate, and the organic layer was dried with magnesium sulfate. The solvent was distilled off under reduced pressure, and the residue was purified by column chromatography filled with silica gel to obtain compound 2 (20.54 g).
[0144] Synthesis Example 3 (Synthesis of compound 3) Compound 3 was synthesized according to the following reaction.
[0145] [ka]
[0146] Into a three-neck flask purged with argon, compound 2 (13.00 g) obtained in Synthesis Example 2 above and dehydrated dichloromethane (70 ml) were placed and stirred at 0° C. for 10 minutes, after which boron trifluoride diethyl ether complex (BF 3 ·OEt 2 ) (6.70 ml) was added dropwise and stirred at room temperature for 2 hours. Water was then added to the reaction solution, which was then extracted with dichloromethane, and the organic layer was dried over magnesium sulfate. The solvent was removed under reduced pressure, and the residue was purified by column chromatography packed with silica gel to obtain compound 3 (8.62 g).
[0147] Synthesis Example 4 (Synthesis of compound 4) Compound 4 was synthesized according to the following reaction.
[0148] [ka]
[0149] Compound 3 (21.25 g) obtained in the above Synthesis Example 3 and dehydrated dichloromethane (200 ml) were placed in an argon-substituted three-necked flask and stirred at 0°C for 10 minutes, after which bromine (2.20 ml) was added dropwise and stirred at room temperature for 8 hours. After that, an aqueous solution of sodium bicarbonate was added to the reaction solution, which was then washed with sodium thiosulfate. After extraction with dichloromethane, the organic layer was dried over magnesium sulfate. The solvent was removed under reduced pressure, and the residue was recrystallized with dichloromethane and methanol to obtain compound 4 (15.24 g).
[0150] Synthesis Example 5 (Synthesis of Compound 5) Compound 5 was synthesized according to the following reaction.
[0151] [ka]
[0152] Compound 4 (10.00 g) obtained in the above Synthesis Example 4 and dehydrated tetrahydrofuran (200 ml) were placed in an argon-substituted three-necked flask and stirred at -48°C for 10 minutes. Then, 10 ml of a 2.8 M hexane solution of n-butyllithium (n-BuLi) was added dropwise, and the mixture was stirred at -48°C for 30 minutes, after which 10 ml of methyl ethyl ketone (MEK) was added dropwise and stirred at room temperature for 1 hour. Then, water was added to the reaction solution, and the mixture was extracted with ethyl acetate, and the organic layer was dried over magnesium sulfate. The solvent was distilled off under reduced pressure, and the residue was purified by column chromatography filled with silica gel to obtain compound 5 (7.67 g).
[0153] Synthesis Example 6 (Synthesis of compound 6) Compound 6 was synthesized according to the following reaction.
[0154] [ka]
[0155] Into a three-neck flask purged with argon, compound 5 (10.00 g) obtained in Synthesis Example 5 above and dehydrated dichloromethane (18 ml) were placed and stirred at 0° C. for 10 minutes. 2 SiH (4.00 ml) was added dropwise and stirred at 0°C for 10 minutes. Then, trifluoroacetic acid (TFA) (2.00 ml) was added dropwise and stirred at room temperature for 2 hours. Water was added to the reaction solution, which was then extracted with dichloromethane, and the organic layer was dried over magnesium sulfate. The solvent was removed under reduced pressure, and the residue was purified by column chromatography packed with silica gel to obtain compound 6 (5.42 g).
[0156] Synthesis Example 7 (Synthesis of compound 7) Compound 7 having the following structure was synthesized in the same manner as described in "Intermediate: Biphenyl-4-yl (9,9-dimethyl-9H-fluoren-2-yl) [4- (4,4,5,5-tetramethyl- [1,3,2] dioxaborolan-2-yl) phenyl] amine" in JP2017-513815A (WO 2015 / 131976).
[0157] [ka]
[0158] Specifically, biphenyl-4-yl(9,9-dimethyl-9H-fluoren-2-yl)amine (40 g) and 4-chloroiodobenzene (26.4 g) were dissolved in toluene (700 mL). The solution was degassed and purified with N 2 The mixture was then saturated with toluene and water. Then, 4.4 mL of a 1 M solution of tri-tert-butylphosphine and palladium(II) acetate (0.5 g) were added to the above solution, followed by the addition of sodium tert-butoxide (15.9 g) to prepare a reaction mixture. The reaction mixture was heated to boiling under a protective atmosphere for 5 hours. The mixture was then partitioned between toluene and water, and the organic phase was washed three times with water and sodium tert-butoxide was added. 2 SO 4The mixture was dried at 400° C. and concentrated by rotary evaporation to obtain a crude product. The crude product was filtered through silica gel with toluene, and the remaining residue was recrystallized from heptane / toluene to obtain biphenyl-4-yl(4-chlorophenyl)(9,9-dimethyl-9H-fluoren-2-yl)amine. Next, the biphenyl-4-yl(4-chlorophenyl)(9,9-dimethyl-9H-fluoren-2-yl)amine obtained above (20 g), bis(pinacolato)diborane (12.5 g), and potassium acetate (12.5 g) were suspended in dioxane (400 mL). To this suspension, 1,1-bis(diphenylphosphino)ferrocene dichloropalladium(II) complex (1.04 g) was added with DCM to obtain a reaction mixture. The reaction mixture was heated under reflux for 16 hours. After cooling, the organic phase was removed, washed three times with 200 mL of water, and concentrated to dryness. The residue was recrystallized from toluene.
[0159] Synthesis Example 8 (Synthesis of compound 8) Compound 8 was synthesized according to the following reaction.
[0160] [ka]
[0161] Into a three-neck flask purged with argon, compound 4 (3.00 g) obtained in Synthesis Example 4 above, compound 7 (3.20 g) obtained in Synthesis Example 7 above, potassium carbonate (2.20 g), 50 mL of dioxane, and 25 mL of water were added and stirred for 30 minutes. Then, tetrakis(triphenylphosphine)palladium(0) (Pd[PPh 3 ] 4 ) (0.30 g) was added and the mixture was heated under reflux and stirred for 13 hours. After the reaction was completed, the mixture was cooled to room temperature and extracted with toluene. The organic layer was dried over magnesium sulfate, filtered, and concentrated. The residue was recrystallized from dichloromethane and ethanol to obtain compound 8 (4.82 g).
[0162] Synthesis Example 9 (Synthesis of Compound 9) Compound 9 was synthesized by the following reaction in the same manner as in Synthesis Example 1 above, except that 1-bromo-4-iodobenzene was used instead of 1-bromo-2-iodobenzene.
[0163] [ka]
[0164] Synthesis Example 10 (Synthesis of compound 10) Compound 10 was synthesized by the following reaction in the same manner as in Synthesis Example 5, except that Compound 9 obtained in Synthesis Example 9 was used instead of Compound 4.
[0165] [ka]
[0166] Synthesis Example 11 (Synthesis of Compound 11) Compound 11 was synthesized by the following reaction in the same manner as in Synthesis Example 6, except that compound 10 obtained in Synthesis Example 10 was used instead of compound 5 in Synthesis Example 6.
[0167] [ka]
[0168] Synthesis example M-1 (Synthesis of compound M-1) Compound M-1 was synthesized according to the following reaction.
[0169] [ka]
[0170] Into a three-neck flask purged with argon, compound 6 (5.50 g) obtained in Synthesis Example 6 above, bispinacol diborate (Bipin) (10.10 g), potassium acetate (5.22 g), tris(dibenzylideneacetone)dipalladium (Pd 2 (dba) 3 ) (0.92 g), 2-dicyclohexylphosphino-2',4',6'-triisopropylbiphenyl (XPhos) (1.02 g), and 1,4-dioxane (200 mL) were added and refluxed under nitrogen atmosphere for 8 hours. The reaction solution was cooled to room temperature, and the solid was filtered off using Celite. The solvent was distilled off under reduced pressure, and the residue was dissolved in toluene, and activated carbon and zeolite were added, and the mixture was stirred at 130°C for 30 minutes. The solid was filtered off using Celite, and the solvent was distilled off under reduced pressure, and the residue was recrystallized from toluene and ethanol to obtain compound M-1 (5.02 g).
[0171] Synthesis example M-2 (Synthesis of compound M-2) Compound M-2 was synthesized according to the following reaction.
[0172] [ka]
[0173] Into a three-neck flask purged with argon, compound 8 (4.10 g) obtained in Synthesis Example 8 above, bis-pinacol diborate (2.29 g), potassium acetate (1.10 g), tris(dibenzylideneacetone)dipalladium (Pd 2 (dba) 3 ) (0.20 g), 2-dicyclohexylphosphino-2',4',6'-triisopropylbiphenyl (XPhos) (0.2 g), and 1,4-dioxane (40 mL) were added and refluxed under nitrogen atmosphere for 8 hours. The reaction solution was cooled to room temperature, and the solid was filtered off using Celite. The solvent was distilled off under reduced pressure, and the residue was dissolved in toluene, and activated carbon and zeolite were added, and the mixture was stirred at 130°C for 30 minutes. The solid was filtered off using Celite, and the solvent was distilled off under reduced pressure, and the residue was recrystallized from toluene and ethanol to obtain compound M-2 (2.10 g).
[0174] Synthesis example M-3 (Synthesis of compound M-3) Compound M-3 was synthesized by the following reaction in the same manner as in Synthesis Example M-1, except that Compound 11 obtained in Synthesis Example 11 was used instead of Compound 6 in Synthesis Example M-1.
[0175] [ka]
[0176] Example 1 (Synthesis of copolymer P-1) Under an argon atmosphere, compound M-1 (2.027 g) obtained in the above Synthesis Example M-1, 2,7-dibromo-9,9-di-n-octylfluorene (1.148 g), palladium acetate (6.4 mg), tris(2-methoxyphenyl)phosphine (51.9 mg), toluene (64 mL), and 20% by mass tetraethylammonium hydroxide aqueous solution (7.3 g) were added to a four-neck flask and stirred at 85 ° C for 6 hours. Next, phenylboronic acid (343 mg), dichlorobis(triphenylphosphine)palladium (119 mg), and 20% by mass tetraethylammonium hydroxide aqueous solution (7.42 g) were added and stirred for 6 hours. Then, sodium N,N-diethyldithiocarbamate trihydrate (5.71 g) dissolved in ion-exchanged water (50 mL) was added and stirred at 85 ° C for 2 hours. After separating the organic layer from the water layer, the organic layer was washed with water, a 3% by mass aqueous solution of acetic acid, and water. The organic layer was passed through a column chromatography packed with silica gel / alumina, and the solvent was distilled off under reduced pressure. The resulting liquid was dropped into methanol, and the precipitated solid was dissolved in toluene, dropped into methanol to precipitate, and the precipitated solid was filtered and dried to obtain copolymer P-1 (0.83 g). The weight average molecular weight (Mw) and dispersity (Mw / Mn) of the obtained copolymer P-1 were measured by SEC. As a result, the weight average molecular weight (Mw) and dispersity (Mw / Mn) of copolymer P-1 were 5,200 and 1.57, respectively.
[0177] The copolymer P-1 thus obtained is presumed to have the following repeating units based on the monomer charging ratio.
[0178] [ka]
[0179] Example 2 (Synthesis of copolymer P-2) Under an argon atmosphere, compound M-2 (1.157 g) obtained in the above Synthesis Example M-2, 2,7-dibromo-9,9-di-n-octylfluorene (0.581 g), palladium acetate (2.4 mg), tris(2-methoxyphenyl)phosphine (19.4 mg), toluene (35 mL), and 20% by mass tetraethylammonium hydroxide aqueous solution (5.4 g) were added to a four-neck flask and stirred at 85 ° C for 6 hours. Next, phenylboronic acid (128.2 mg), dichlorobis(triphenylphosphine)palladium (44 mg), and 20% by mass tetraethylammonium hydroxide aqueous solution (5.4 g) were added and stirred for 6 hours. Then, sodium N,N-diethyldithiocarbamate trihydrate (5.71 g) dissolved in ion-exchanged water (30 mL) was added and stirred at 85 ° C for 2 hours. After separating the organic layer from the water layer, the organic layer was washed with water, 3% by mass aqueous acetic acid solution, and water. The organic layer was passed through a column chromatography packed with silica gel / alumina, and the solvent was distilled off under reduced pressure. The resulting liquid was dropped into methanol, and the precipitated solid was dissolved in toluene, dropped into methanol to precipitate, and the precipitated solid was filtered and dried to obtain copolymer P-2 (1.01 g). The weight average molecular weight (Mw) and dispersity (Mw / Mn) of the obtained copolymer P-2 were measured by SEC. As a result, the weight average molecular weight (Mw) and dispersity (Mw / Mn) of copolymer P-2 were 17,600 and 1.72, respectively.
[0180] The copolymer P-2 thus obtained is presumed to have the following repeating units based on the monomer charging ratio.
[0181] [ka]
[0182] Comparative Example 1 (Synthesis of Comparative Copolymer P-3) Under an argon atmosphere, compound M-3 (1.607 g) obtained in the above Synthesis Example M-3, 2,7-dibromo-9,9-di-n-octylfluorene (1.599 g), palladium acetate (6.5 mg), tris(2-methoxyphenyl)phosphine (53.2 mg), toluene (60 mL), and 20% by mass tetraethylammonium hydroxide aqueous solution (15.03 g) were added to a four-neck flask and stirred at 85 ° C for 6 hours. Next, phenylboronic acid (352.7 mg), dichlorobis(triphenylphosphine)palladium (122.8 mg), and 20% by mass tetraethylammonium hydroxide aqueous solution (5.4 g) were added and stirred for 6 hours. Then, sodium N,N-diethyldithiocarbamate trihydrate (7.21 g) dissolved in ion-exchanged water (30 mL) was added and stirred at 85 ° C for 2 hours. After separating the organic layer from the water layer, the organic layer was washed with water, 3% by mass aqueous acetic acid solution, and water. The organic layer was passed through a column chromatography packed with silica gel / alumina, and the solvent was distilled off under reduced pressure. The resulting liquid was dropped into methanol, and the precipitated solid was dissolved in toluene, and dropped into methanol to precipitate. The precipitated solid was filtered and dried to obtain comparative copolymer P-3 (1.21 g). The weight average molecular weight (Mw) and dispersity (Mw / Mn) of the obtained comparative copolymer P-3 were measured by SEC. As a result, the weight average molecular weight (Mw) and dispersity (Mw / Mn) of copolymer P-2 were 7,400 and 1.85, respectively.
[0183] The comparative copolymer P-3 thus obtained is presumed to have the following repeating units based on the monomer charging ratio.
[0184] [ka]
[0185] Example 3 (Fabrication of electroluminescent element 1) A glass substrate with indium tin oxide (ITO) patterned to a thickness of 150 nm was used as the first electrode (anode). This glass substrate with ITO was washed sequentially with a neutral detergent, deionized water, water, and isopropyl alcohol, and then subjected to UV-ozone treatment. Next, poly(3,4-ethylenedioxythiophene) / poly(4-styrenesulfonate) (PEDOT / PSS) (Sigma-Aldrich) was applied to the glass substrate with ITO by spin coating so that the dry thickness was 30 nm, and then dried. As a result, a hole injection layer with a thickness (dry thickness) of 30 nm was formed on the glass substrate with ITO.
[0186] Next, the copolymer P-1 (hole transport material) synthesized in Example 1 was dissolved in toluene (solvent) at a concentration of 1% by mass to prepare a hole transport layer forming coating solution (1). This hole transport layer forming coating solution (1) was applied to the hole injection layer formed above by spin coating so as to have a thickness (dry film thickness) of 30 nm, and then heated at 230° C. for 1 hour to form a hole transport layer having a thickness (dry film thickness) of 30 nm on the hole injection layer.
[0187] In cyclohexane, the following structure:
[0188] [ka]
[0189] A quantum dot dispersion liquid was prepared by dispersing blue quantum dots of ZnTeSe / ZnSe / ZnS (core / shell / shell; average diameter = about 10 nm) having the above structure to a concentration of 1.0 mass %. The hole transport layer (particularly copolymer P-1) does not dissolve in cyclohexane. This quantum dot dispersion liquid was applied to the hole transport layer by spin coating so that the dry film thickness was 30 nm, and then dried. As a result, a quantum dot light-emitting layer having a thickness (dry film thickness) of 30 nm was formed on the hole transport layer. The light emitted by irradiating the quantum dot dispersion liquid with ultraviolet light had a central wavelength of 462 nm and a half-width of 30 nm.
[0190] This quantum dot light-emitting layer was completely dried. On this quantum dot light-emitting layer, lithium quinolate (Liq) and 1,3,5-tris(N-phenylbenzimidazol-2-yl)benzene (TPBI) (Sigma-Aldrich) as an electron transport material were co-deposited using a vacuum deposition apparatus. As a result, an electron transport layer with a thickness of 36 nm was formed on the quantum dot light-emitting layer.
[0191] Using a vacuum deposition apparatus, (8-quinolinolato)lithium (lithium quinolate) (Liq) was deposited on the electron transport layer, resulting in the formation of an electron injection layer having a thickness of 0.5 nm on the electron transport layer.
[0192] On the electron injection layer formed above, aluminum (hereinafter, Al) was evaporated using a vacuum evaporation apparatus to form a second electrode (cathode) having a thickness of 100 nm on the electron injection layer, thereby obtaining an electroluminescent element 1 (quantum dot electroluminescent element 1).
[0193] Example 4 (Fabrication of electroluminescent element 2) An electroluminescent device 2 (quantum dot electroluminescent device 2) was produced in the same manner as in Example 3, except that the copolymer P-2 synthesized in Example 2 was used instead of the copolymer P-1 in Example 3.
[0194] Comparative Example 1 (Preparation of Comparative Electroluminescent Device 1) In Example 3, except that the comparative copolymer P-3 synthesized in Comparative Example 1 was used instead of the copolymer P-1, the same operation as in Example 3 was carried out to prepare a comparative electroluminescent element 1 (comparative quantum dot electroluminescent element 1).
[0195] [Evaluation of electroluminescent device] The luminous efficiency (EQE) and luminous lifetime (LT90) of electroluminescence elements 1 and 2 prepared in Examples 3 and 4 and comparative electroluminescence element 1 prepared in Comparative Example 1 were evaluated by the following method. The results are shown in Table 1 below. Note that the LT90 in Table 1 below is shown as a relative value, with the LT90 [hr] of comparative electroluminescence element 1 in Comparative Example 1 taken as 1.
[0196] (Luminous efficiency) When a voltage is applied to each electroluminescent element, a current begins to flow at a constant voltage, causing the electroluminescent element to emit light. Using a DC constant voltage power supply (Keyence Corporation, source meter), the voltage is gradually increased for each element, the current value at that time is measured, and the luminance during emission is measured using a luminance measuring device (Topcon, SR-3). The measurement is stopped when the luminance begins to decay. The current value (current density) per unit area is calculated from the area of each element, and the luminance (cd / m 2 ) to current density (A / m 2 ) to calculate the current efficiency (cd / A).
[0197] In addition, the external quantum efficiency (EQE) (%) at Cd / A max is calculated from the spectral radiance spectrum measured by the luminance measuring device, assuming that Lambertian radiation is used, and the luminous efficiency is evaluated.
[0198] (Light Emitting Life) A DC constant voltage power supply (Keyence Corporation, source meter) was used to apply a predetermined voltage to each electroluminescent element, causing each quantum dot electroluminescent element to emit light. The light emission of the quantum dot electroluminescent element was measured with a brightness measuring device (Topcon Corporation, SR-3), while the current was gradually increased until the brightness reached 280 nit (cd / m 2 ), the current is made constant and left as is. The luminance value measured with a luminance measuring device gradually decreases, and the time it takes for the luminance to reach 90% of the initial luminance is defined as "LT90(hr)."
[0199] [Table 1]
[0200] From the results in Table 1 above, it can be seen that the electroluminescent elements 1 and 2 of Examples 3 and 4 can achieve a good balance between the luminous efficiency (EQE) and the luminous lifetime (LT90) compared to the comparative electroluminescent element 1. In this example, a blue quantum dot electroluminescent element was evaluated, but it is considered that the same results as above can be obtained also in a red quantum dot electroluminescent element, etc.
[0201] Although the present invention has been described above with reference to embodiments and examples, the present invention is not limited to the specific embodiments and examples, and various modifications and changes are possible within the scope of the invention described in the claims. [Explanation of symbols]
[0202] 100...Electroluminescence element (EL element), 110...substrate, 120...first electrode, 130...hole injection layer, 140...hole transport layer, 150...light-emitting layer, 160...electron transport layer, 170...electron injection layer, 180...Second electrode.
Claims
1. A copolymer having a structural unit represented by the following formula (1): 【Chemistry 1】 In the above formula (1), R 1 is an unsubstituted branched alkyl group having 3 to 5 carbon atoms, or -Y-N(Ar 2 ) (Ar 3 ), where Y represents an unsubstituted phenylene group, Ar 2 and Ar 3 each independently represents a fluorenyl group substituted by two alkyl groups having 1 to 3 carbon atoms, or an unsubstituted biphenyl group; R2 is a fluorene ring formed by bonding two phenyl groups together; X1 represents a carbon atom (C); Ar 1 is a group selected from the following formula (5): 【Chemistry 2】 In the above formula (5), Q represents -CR 5 R 6 -, where R 5 and R 6 each independently represent an unsubstituted alkyl group having 1 to 20 carbon atoms; * denotes the binding site that forms the main chain.
2. The copolymer according to claim 1, wherein the constitutional unit represented by the formula (1) is a constitutional unit represented by the following formula (1'): 【Chemistry 3】 In the above formula (1'), R 1 and Ar 1 are defined as in the constitutional unit represented by the above formula (1).
3. A copolymer according to claim 1 or 2, which is the following copolymer P-1 or the following copolymer P-2. 【Chemistry 4】
4. An electroluminescence device material comprising the copolymer according to any one of claims 1 to 3.
5. An electroluminescence element comprising a first electrode, a second electrode, and one or more organic films disposed between the first electrode and the second electrode, 4. An electroluminescence device, wherein at least one layer of the organic film comprises the copolymer according to claim 1.
6. The electroluminescence device according to claim 5 , wherein the organic film containing the copolymer is a hole transport layer or a hole injection layer.
7. 7. The electroluminescence device according to claim 5, wherein the organic film has a light-emitting layer containing semiconductor nanoparticles or an organometallic complex.
Citation Information
Patent Citations
Indolo [3, 2, 1-kl] phenoxazine compound, preparation method and application thereof, and electronic device
CN111704624A
Quantum point light emitting element with multiple quantum point layer
JP2010199067A
Polymer compound, composition, liquid composition, thin film, electroluminescent element material and electroluminescent element
JP2018104675A
Organic light-emitting compound and organic light-emitting device using same
KR1020140027030A
Conjugated compounds containing hydroindoloacridine structural elements, and their use
US20090136779A1